2015
DOI: 10.1183/23120541.00023-2015
|View full text |Cite
|
Sign up to set email alerts
|

Fungal contamination of the respiratory tract and associated respiratory impairment among sawmill workers in India

Abstract: Wood processing workers are exposed to wood-associated microbiological contaminants, including fungi. Our aim was to study the potential association between sputum fungus and adverse respiratory effects in such workers.In a group of sawmill workers, we administered a respiratory questionnaire, performed lung function testing and quantified the proportions of leukocytes in spontaneously expectorated sputum samples. We identified fungal species by DNA sequencing.Of 54 sawmill workers, 19 yielded fungal positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Airborne fungal particles are recognized as potential health hazards in environments with heavy fungal contamination ( Institute of Medicine, 2004 ). A number of studies from sawmills have revealed associations between fungal exposure and respiratory impairments such as hypersensitivity pneumonitis, organic dust syndrome (ODTS), and occupational asthma ( Belin, 1987 ; Dahlqvist et al, 1992 ; Eduard et al, 1992 ; Halpin et al, 1994 ; Rask‐Andersen et al, 1994 ; Mandryk et al, 2000 ; Adhikari et al, 2015 ). Fungal spores and related biomarkers are commonly measured during fungal exposure assessment whether in indoor or occupational settings.…”
Section: Introductionmentioning
confidence: 99%
“…Airborne fungal particles are recognized as potential health hazards in environments with heavy fungal contamination ( Institute of Medicine, 2004 ). A number of studies from sawmills have revealed associations between fungal exposure and respiratory impairments such as hypersensitivity pneumonitis, organic dust syndrome (ODTS), and occupational asthma ( Belin, 1987 ; Dahlqvist et al, 1992 ; Eduard et al, 1992 ; Halpin et al, 1994 ; Rask‐Andersen et al, 1994 ; Mandryk et al, 2000 ; Adhikari et al, 2015 ). Fungal spores and related biomarkers are commonly measured during fungal exposure assessment whether in indoor or occupational settings.…”
Section: Introductionmentioning
confidence: 99%
“…Given the significant burning of wood outside the home, health programmes designed to improve air quality must expand their current focus on rural women living BPL to include the burning of scrap wood from sawmills and the workplace dust and pollutants that men, women and children breathe while living and/or working at a brick kiln, an indoor sawmill or other sites where firewood is burned. Indoor and ambient air quality and lack of use of personal protective equipment are closely linked to various respiratory and skin ailments among workers in sawmills and kilns (Adhikari et al, 2015;Sain & Meena, 2017). And yet, cookstove improvement projects tend to assume that cookstoves will not only improve women's health but liberate them to engage in wage-earning work.…”
Section: Discussionmentioning
confidence: 99%
“…Being respirable by size (2-10 µm), fungal spores can easily enter the human respiratory tract [67]. Fungus-induced allergic respiratory symptoms can occur from the indoor, occupational environment or both [3,9]. Throughout the world, 20-30% of the allergic problems are attributable to fungal spores, which include 44% atopic and 80% among asthmatics [60].…”
Section: Introductionmentioning
confidence: 99%